Pan & M. Kosicki’s Framing Analysis: Death of Al-Jazeera Journalist in Gaza - Istifarin, Afianti; Basid, Abdul (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2025)
Framing is the framing of a media in constructing and broadcasting news in society. The objectives of this research are: (1) Syntactic study of news coverage of the death of Al-Jazeera journalists in Gaza; (2) Script of news coverage of the death of Al-Jazeera journalists in Gaza; (3) Thematic coverage of the death of journalists in Gaza; (4) Rhetorical coverage of news coverage of the death of journalists in Gaza. This research uses a qualitative method whose data comes from two news texts from the BBC and CNN Arabic. This data was collected through reading and note-taking techniques and analyzed using Milles & Huberman's analysis style. The results of this study found several important things related to the news coverage of the death of Al-Jazeera journalists in Gaza: (1) the syntactic structure in the news coverage emphasizes the humanitarian aspect and the impact of the conflict, (2) news scripts often highlight the importance of press freedom and journalists' security, (3) the thematic of journalists' deaths in Gaza is often associated with human rights and security issues in conflict zones, (4) rhetorical techniques are used to evoke empathy and emphasize the important role of journalists. This research offers a new perspective on the effective and impactful delivery of news coverage of journalist deaths and how such coverage can raise awareness and gain widespread support for the protection of journalists. Abstrak Framing merupakan pembingkaian suatu media dalam mengkonstruksi dan menyiarkan berita di masyarakat. Tujuan penelitian ini adalah: (1) Kajian sintaksis liputan berita kematian wartawan Al-Jazeera di Gaza; (2) Naskah liputan berita kematian wartawan Al-Jazeera di Gaza; (3) Liputan tematik kematian wartawan di Gaza; (4) Liputan retoris liputan berita kematian wartawan di Gaza. Penelitian ini menggunakan metode kualitatif yang datanya bersumber dari dua teks berita BBC dan CNN Arabic. Data ini dikumpulkan melalui teknik baca dan catat serta dianalisis menggunakan gaya analisis Milles & Huberman. Hasil penelitian ini menemukan beberapa hal penting terkait pemberitaan kematian jurnalis Al-Jazeera di Gaza: (1) struktur sintaksis dalam pemberitaan tersebut menekankan pada aspek kemanusiaan dan dampak konflik, (2) naskah berita sering menonjolkan pentingnya kebebasan pers dan keamanan jurnalis, (3) tema kematian jurnalis di Gaza sering dikaitkan dengan isu hak asasi manusia dan keamanan di zona konflik, (4) teknik retorika digunakan untuk membangkitkan empati dan menekankan peran penting jurnalis.